Growth differentiation factor 15 performance as a novel non-invasive circulating biomarker of liver damage in paediatric non-alcoholic fatty liver disease - Mosca, A.; Braghini, M.R.; Andolina, G.; Comparcola, D.; Alterio, A.; Sartorelli, M.R.; Monti, L.; Maggiore, G.; Alisi, A.; Panera, N. (Digestive and liver disease, 2024)
To date, non-alcoholic fatty liver disease is considered the most common chronic hepatopathy worldwide. NAFLD spectrum is comprehensive of simple fatty liver (FLT) that may progress to non-alcoholic fatty steatohepatitis (NASH) even in the presence or absence of fibrosis. Several circulating factors, such as the recent growth differentiation factor 15 (GDF15), have been investigated as promising biomarkers of liver fibrosis. However, studies investigating whether plasma levels of GDF15 might be associated with fibrosis in children with NAFLD are still poor. Here, we evaluated the ability of GDF15 plasma levels as surrogate biomarkers of liver damage in children affected by liver biopsy-proven NAFLD, The study was performed on available samples of 124 adolescents (mean age 13.36 years ± 3.36), 77 (62%) males, who underwent liver biopsy for NAFLD between 2014 to 2021, and 24 healthy controls evaluated at the Hepatology Unit of the “Bambino Gesù” Children's Hospital. Plasma levels of GDF15 were assessed by a commercially available enzyme-linked immunosorbent assay (ELISA) assay. Our results revealed that children with NAFLD exhibited higher median levels of circulating GDF15 (p<0.0001) than control subjects. GDF15 plasma levels in the NAFLD population correlated positively with steatosis (r=0.25, p=0.015), fibrosis (r=0.42, p=0.001), and inflammation (r=0.25, p=0.008) but not with ballooning. Moreover, circulating levels of GDF15 correlated with other metabolic parameters, and insulin resistance was measured as a homeostasis model assessment of insulin resistance (r=0.41, p=0.0001). Of note at multivariate regression analysis, after adjusting for body mass index, age, and gender, only the correlation of GDF15 levels with fibrosis and metabolic parameters was confirmed. In conclusion, our results suggest that plasma levels of GDF15 could be potential biomarkers for NAFLD-related fibrosis in adolescents, although further studies are needed to better define its relationship with fibrosis and insulin resistance.